Evolution of Non-religious Functions of Catholic Sanctuaries in the Eastern Borderland of Poland – From Patriotic Manifestations to Interfaith Dialogue and Integration - Małgorzata Flaga (Archiwa, Biblioteki i Muzea Kościelne)
The paper concerns two significant, non-religious but social functions of Polish Catholic worship centres, namely: patriotic and integrative role. This issue is discussed on the basis of the selected sanctuaries of the eastern borderland of Poland, precisely in the Lublin province. In the past, it was multicultural and multidenominational area and presently it is famous for its rich history and cultural heritage reflected in, among other things, religious centres. The description of the sanctuaries proves their commitment in the political and social life of Poland. The spiritual guardians of the sanctuaries always manifested strong patriotic attitude that corresponded with national events and needs. At various stages of the history, religious centres actively participated in initiatives and the matters of the entire nation. Those traditions survived until today as the current activities of the regional sanctuaries are still closely related to the socio-political situation of the country. But the essential task of the Church is not any longer to urge the Poles to fight for independence, but to work towards mutual knowledge, understanding as well as uniting the local, multi-faith communities.